Creutzfeldt-Jakob Disease with Mixed Transcortical Aphasia: Insights into Echolalia - S. E. McPherson; J. D. Kuratani; J. L. Cummings; J. Shih; P. S. Mischel; H. V. Vinters (Behavioural Neurology)
Aphasia is a common manifestation of Creutzfeldt-Jakob disease (CJD), and investigation of the linguistic disorders of CJD patients may provide insights into the neurobiological mechanisms of language and aphasia. We report an autopsy-confirmed case of CJD in which the presenting symptom was change in language abilities. The patient ultimately evidenced mixed transcortical aphasia (MTA) with echolalia. Disruption of frontal-subcortical circuits with environmental dependency accounts for the symptoms in MTA, including intact repetition and echolalia. Observation in this patient and a review of the literature suggest that frontal-subcortical circuit dysfunction may contribute to the syndrome of echolalia. This hypothesis offers an alternative explanation to “isolation” of the speech area as the cause of MTA.